A Hubungan Indeks Massa Tubuh (IMT) dan Lingkar Pinggang terhadap Ketahanan Kardiorespirasi pada Siswa SMA Methodist 1 Medan, Sumatera Utara Tahun 2023–2024.: HUBUNGAN INDEKS MASSA TUBUH (IMT) DAN LINGKAR PINGGANG TERHADAP KETAHANAN KARDIORESPIRASI PADA SISWA SMA METHODIST 1 MEDAN SUMATERA UTARA 2023-2024 - Jeremia Simanjuntak; Suryati Sinurat; Alexander Parlindungan Marpaung; Menang Bastanta Tarigan; Jekson Martiar Siahaan (Universitas Methodist Indonesia, 2024)
ABSTRACT Currently, modern life, especially in urban areas, promotes an instant consumption lifestyle, particularly among teenagers. With technological advancements, teenagers can easily order fast food through delivery apps, making fast food a common choice. In addition to fast food, school snacks are also highly favored by teenagers. This excessive consumption pattern, if sustained over time, can lead to fat accumulation that affects body mass index (BMI) and waist circumference. According to the 2019 health profile, 35.4% of teenagers experience obesity, with the highest prevalence in urban areas at 25.1%. Excess fat accumulation puts pressure on cardiorespiratory function, reducing lung capacity as reflected in VO2Max or cardiorespiratory endurance. This decline in cardiorespiratory endurance significantly affects a person's quality of life, causing them to feel fatigued easily and limiting their ability to engage in prolonged physical activities.Conclusion: There is a significant relationship between body mass index and waist circumference on cardiorespiratory endurance among students of Methodist 1 High School, Medan, North Sumatra..